The foundation of the Institute of Paediatric Virology on the island of Euboea, Greece (Review) - Mammas, Ioannis N. (Exp Ther Med, 2020)
The Institute of Paediatric Virology, founded on October 2019 on the island of Euboea in Greece, introduces medical students, paediatric and neonatal trainees, postgraduate students, virologists, paediatric and allied health professionals to the bold, new, scientific field of paediatric virology. The institute is committed to medical education and is the sequel of the Paediatric Virology Study Group (PVSG), which was formed in 2007 in the United Kingdom by a group of young paediatric trainees and junior researchers. The main mission of the institute is to provide an educational e-platform on neonatal and paediatric viral infections, to facilitate scientific discussion between virologists and paediatric health professionals and to develop an international network aiming to the promotion of children's health by the prevention and treatment of viral infectious diseases. The foundation of the institute is dedicated to three children from a small fishing village at the south of the island of Euboea in Greece, who survived the 1918 Spanish flu pandemic.